CONTRIBUTION TO THE DISCUSSION ON THE EU LEGAL ORDER AS A SELF-CONTAINED LEGAL REGIME - Đorđević Aleksovski, Sanja M. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Since the process of fragmentation of international public law has enabled the formation of numerous legal regimes, the question of the qualification of the legal order of the European Union (EU) arises. Namely, for a long time it was not percieved as an self-contained regime, to which the classification of the International Law Commission’s Report “Fragmentation of International Law: Difficulties arising from Diversification and Dissemination of International Law“ indirecly contributed. This Report classifies the EU legal order within the section on regionalization, thus relativizing it by reducing it to the cooperation of states determined only by geographical criteria. Although indisputable, the geographical criterion is of secondary value to a number of other arguments that take into account its qualitative dimension. Therefore, the paper raises the key question of whether the EU legal order has reached such a level of development and quality that it can be considered an self-contained legal regime. In the search for answers to the research question, the paper analyzes arguments pro et contra.Arguments against the notion of the EU legal order as an self-contained legal regime relate to: the omnipresence of general international public law, which necessarily implies the connection of the specialized EU law with general international law. In addition, the arguments of the origin, subjects and the manner of creating EU law are emphasized, because they are inseparable from the international law, which is why it is denied the characteristic of independence. By emphasizing these arguments, there is a thesis that EU law is and remains only a subsystem of international law, which would be especially be visible in the case of inadequate regulation of state responsibility in EU law. In such situations, it would be necessary to resort to the provisions of international public law (so-called fall-back).On the other hand, arguments in favor of the independence of the EU legal order are analyzed and emphasized. Without denying the fact that the EU legal order evolved from international public law, that it represented a nasciturus within it, was based on an international treaty, and that the EU itself represents an international organization, the fact of its decades-long evolutionary development must be accepted. a greater degree of autonomy than general international public law, which is confirmed and supported by case law and attitudes from the doctrine. In addition, the specific way of filling legal gaps with solutions from EU law itself, and not by applying the logic of the fall-back system, speaks in favor of the autonomy of the EU legal order. All this points to the exceptionality and uniqueness of the EU legal order, as well as its completeness.Therefore, even if there were arguments in favor of imperfection and incompleteness of the EU legal order, its dynamic development leads us to the conclusion that it is at such a developmental and qualitative stage today that it should be recognized as an self-contained legal regime.
Keywords: fragmentation; EU legal order; self-contained legal regime; autonomy